Profile Psychological Well-Being High school Students - Vivin Ariyanti; Bakhrudin Al Habsy; Mochamad Nursalim; Retno Tri Hariastuti (Bisma The Journal of Counseling, 2023)
Lack of awareness of the importance of psychological well-being makes individuals decide to take negative actions that will harm themselves and cannot achieve happiness. Psychological well-being is one indicator of achieving individual happiness. When individuals are able to achieve happiness, their life needs will also be fulfilled. This research was conducted with the aim of analyzing the level of psychological well-being in high school students in Surabaya. This research uses a quantitative approach using a survey design. The subjects in this research were 191 high school students in grades X, XI and XII, using a random sampling method. The data collection method uses a closed questionnaire. The research instrument used was a closed questionnaire based on Ryff's scales of Psychological well-being theory to measure the level of psychological well-being with a validity level of 0.659 and an r value of 0.655. Data analysis uses descriptive quantitative analysis. The results obtained after the analysis were carried out were that 70.2% of students were in the medium category, so the majority of students had psychological well-being scores that were in the medium category.